Pengaruh Model Pembelajaran Problem Posing Terhadap hasil Belajar Kognitif Fisika Siswa Kelas VII MTs PP Raudatussalam Rambah Pada Konsep Besaran Dan Satuan - Hasibuan, Elmi sari (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2016)
This research discusses the influence Problem Posing learning model against the cognitive learning physics VII grade students MTs PP Raudatussalam Rambah on the concept of quantity and unit. Population in this research is class VII MTs PP Raudhatussalam Rambah Rokan Hulu, while its sample is classVII (seven) as many as 22 students of MTs PP Raudatussalam Rambah. Of the learning objectives are testedin the classical style, where over 80% mastery of the entire student learning objectives to be achieved, it can be said that the learning objective have been completed. Based on the data analys, that the test results of classical completeness gain mastery by 95%, and the results of the normalized gain, low gain value is 0.50 which is categorized as moderate and gain the highest value is 0.87 categorized as high. As well as gained an average value of 0.74 which included a gain that is considered high. Problem Posing learning model that has done a good effect on the cognitive learning physics class VII MTs PP Raudatussalam Rambah.